2021
DOI: 10.1021/acs.est.1c02182
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study about the Photolysis of Nitrates on Mineral Oxides

Abstract: Nitrates formed on mineral dust through heterogeneous reactions in high NO x areas can undergo photolysis to regenerate NO x and potentially interfere in the photochemistry in the downwind low NO x areas. However, little is known about such renoxification processes. In this study, photolysis of various nitrates on different mineral oxides was comprehensively investigated in a flow reactor and in situ diffuse reflectance Fourier-transform infrared spectroscopy (in situ DRIFTS). TiO2 was found much more react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 97 publications
(140 reference statements)
0
45
0
Order By: Relevance
“…A recent lab study of pNO3photolysis on inorganic aerosol suggests a ten-times slower photolysis rate than assumed in simulation M3b (Shi et al, 2021), and a similar reduction was derived from an analysis of NOy partitioning in polluted marine air (Romer et al, 2018). Further 565 lab work has shown that the rate and product yield of this reaction is sensitive to surface composition (Ma et al, 2021). Robust parameterizations will require continued systematic study of controlling factors, preferably under environmentally relevant and near-ambient conditions.…”
Section: Implications For Modelling Biomass Burning Chemistrymentioning
confidence: 76%
See 1 more Smart Citation
“…A recent lab study of pNO3photolysis on inorganic aerosol suggests a ten-times slower photolysis rate than assumed in simulation M3b (Shi et al, 2021), and a similar reduction was derived from an analysis of NOy partitioning in polluted marine air (Romer et al, 2018). Further 565 lab work has shown that the rate and product yield of this reaction is sensitive to surface composition (Ma et al, 2021). Robust parameterizations will require continued systematic study of controlling factors, preferably under environmentally relevant and near-ambient conditions.…”
Section: Implications For Modelling Biomass Burning Chemistrymentioning
confidence: 76%
“…The photolysis frequency for reaction R1 is rescaled from that of gas-phase HNO3 by a factor of 286 following Ye et al (2017Ye et al ( , 2018. The mechanism for this reaction is not well understood (Baergen and Donaldson, 2013), and the efficacy of pNO3 -245 photolysis likely depends on aerosol composition (Ma et al, 2021). Other studies have estimated photolysis frequencies an order of magnitude or more lower in non-biomass burning environments (Romer et al, 2018;Shi et al, 2021).…”
Section: Addition Of Honomentioning
confidence: 99%
“…This may be attributed to the photocatalytic oxidation of NO to NO 2 by superoxide radicals. Additionally, previous studies proposed that O 2 can promote the regeneration of nitrates through photo‐oxidation of gaseous products to reduce the net decomposition of nitrate [9a] . This explains the decrease in the total nitrogen content of the gas phase products in the humid air.…”
Section: Resultsmentioning
confidence: 93%
“…As a result, this phenomenon is attributed to a photochemical process of converting nitrate to nitrite that occurs under the activation of ultraviolet light, thereby achieving a high nitrate removal performance. 155 In some investigations using TiO 2 as a catalyst, the further reduction selectivity of nitrite is considered to be a crucial fork in the regulation of product by ultraviolet light. 156 Studies had shown that when nitrite combines with protons to form nitrous acid, nitrogen is more likely to become the final product for nitrate reduction.…”
Section: Approaches To Regulating Selectivity Of Photocatalytic Nitra...mentioning
confidence: 99%